DAMPAK PENGGANDA SEKTOR INDUSTRI PENGOLAHAN UNGGULAN TERHADAP PEREKONOMIAN NUSA TENGGARA TIMUR - Johny Koylal; Stefanus M. Kuang; Jemseng C. Abineno (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study examines the multiplier effect of output, income, and labor in the processing industry sector in the economy of East Nusa Tenggara. The data used in the study are Gross Regional Domestic Product, number of workers, number of inputs and outputs, number of final demands, and the number of primary inputs of East Nusa Tenggara in 2020 sourced from the Central Statistics Agency. The analysis method used is a quantitative analysis of the East Nusa Tenggara Input-Output Table in 2020 which was compiled from the update of the East Nusa Tenggara Input-Output Table in 2017. The results of the analysis show that the grain milling industry sector and the food and beverage industry sector have high output, income, and labor multiplier values or are above the average multiplier value of all economic sectors. Therefore, these two sectors can be considered as leading processing industry sectors in encouraging the growth of the processing industry sector to continue to make a major contribution to the economy